1987
DOI: 10.1128/mcb.7.5.2031
|View full text |Cite
|
Sign up to set email alerts
|

Strontium phosphate transfection of human cells in primary culture: stable expression of the simian virus 40 large-T-antigen gene in primary human bronchial epithelial cells.

Abstract: Strontium ion formed DNA-phosphate precipitates analogous to those formed by calcium but lacking the lethal and differentiation-inducing effects of calcium on many epithelial cell types in primary culture. Human primary bronchial epithelial cells were transiently and stably transfected by using strontium phosphate; the frequency of stable transformation with a plasmid carrying the simian virus 40 large-T-antigen gene was greater than l0-4.Calcium phosphate transfection has been widely used to introduce cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Moreover, because of the limited effectiveness, DNA:CaPi coprecipitates have been applied to cells for long incubation times in simple NaCl solutions that have led to cell toxicity. 22,26,27 For example, a standard protocol involves treating cells with DNA:CaPi coprecipitates in Hepes-buffered saline (pH 7.1) for 16 h. 15 We also found that with long exposure times CaPi could produce significant cell toxicity. In earlier work, we found that CaPi coprecipitates were relatively effective at binding to cells, and we were able to use this property to enhance markedly delivery of adenovirus to cells that were normally resistant to infection.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, because of the limited effectiveness, DNA:CaPi coprecipitates have been applied to cells for long incubation times in simple NaCl solutions that have led to cell toxicity. 22,26,27 For example, a standard protocol involves treating cells with DNA:CaPi coprecipitates in Hepes-buffered saline (pH 7.1) for 16 h. 15 We also found that with long exposure times CaPi could produce significant cell toxicity. In earlier work, we found that CaPi coprecipitates were relatively effective at binding to cells, and we were able to use this property to enhance markedly delivery of adenovirus to cells that were normally resistant to infection.…”
Section: Discussionmentioning
confidence: 78%
“…doses have previously been shown to delay the induction of mdm-2 expression in murine C127 cells (Perry et al, 1993), and u.v. fails to induce mdm-2 expression in murine keratinocytes in vivo (Burden et al, 1996). Thus repression of mdm-2 expression may contribute to the reportedly higher e cacy of u.v.…”
Section: Discussionmentioning
confidence: 97%
“…Cells growing in 90 mm dishes were transfected by strontium phosphate co-precipitation (Brash et al, 1987). 20 mg of the p53 dependent reporter plasmid pRGCDfoslacZ or pDfos-lacZ control vector (Frebourg et al, 1992) (a gift from S Friend) was co-transfected with 2 mg of either pSV 2 neo (Southern and Berg, 1982) or pC53-SCX3 (Baker et al, 1990), which encodes the temperature sensitive ala 143 mutant of human p53 (Zhang et al, 1994) and the neo gene.…”
Section: Dna Transfectionmentioning
confidence: 99%
“…Transfection was performed by the method of strontium phosphate coprecipitation (Brash et al, 1987). Six hours before transfection, the medium was replaced with 5 ml of warm SF-12 medium (Flow Labs) with 10% fetal calf serum.…”
Section: Transfection Protocolmentioning
confidence: 99%
“…Most success has been achieved with human mammary epithelium and keratinocytes (Brown & Gallimore, 1987;Taylor-Papadimitrou et al, 1982) transformed by SV40. Transformation of human brochial epithelium with SV40 large T (Brash et al, 1987;Reddel et al, 1988), of human uroepithelial cells (Christian et al, 1987) and fetal colonic epithelial cells (Berry et al, 1988) with SV40, and human thyroid epithelium with SV40 early region by electroporation (Whitley et al, 1987) has also been reported. Recently infection with a retrovirus carrying the adenovirus EIA gene has been used to generate a human thyroid cell line (Cone et al, 1988).…”
mentioning
confidence: 99%